2009
DOI: 10.1063/1.3173827
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and accurate approximations to the local coupled cluster singles doubles method using a truncated pair natural orbital basis

Abstract: A production level implementation of the closed-shell local quadratic configuration interaction and coupled cluster methods with single and double excitations (QCISD and CCSD) based on the concept of pair natural orbitals [local pair natural orbital LPNO-QCISD and LPNO-CCSD) is reported, evaluated, and discussed. This work is an extension of the earlier developed LPNO coupled-electron pair approximation (LNPO-CEPA) method [F. Neese et al., Chem. Phys. 130, 114108 (2009)] and makes extended use of the resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
598
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(615 citation statements)
references
References 114 publications
4
598
0
3
Order By: Relevance
“…Alanine Alpha Helix Test Case. To determine the accuracy and performance of the combined FMO-CIM approach relative to standard CIM and canonical correlation methods, FMO2-CIM/MP2, CIM/MP2, and full MP2 (using GAMESS), were applied to the calculation of the electron correlation energy of a 20-residue polyalanine α helix, Ala 20 (using the FMO2-RHF equilibrium geometry). To study the dependence of the FMO2-CIM/MP2 correlation energy and computational wall time with respect to both the FMO fragment size and the CIM subsystem parameter ζ, calculations were performed using two and four alanine residues per FMO fragment (five-and ten-fragment schemes) while also varying the subsystem size parameter ζ from 0.003 to 0.001 hartree.…”
Section: Preliminary Calculations and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alanine Alpha Helix Test Case. To determine the accuracy and performance of the combined FMO-CIM approach relative to standard CIM and canonical correlation methods, FMO2-CIM/MP2, CIM/MP2, and full MP2 (using GAMESS), were applied to the calculation of the electron correlation energy of a 20-residue polyalanine α helix, Ala 20 (using the FMO2-RHF equilibrium geometry). To study the dependence of the FMO2-CIM/MP2 correlation energy and computational wall time with respect to both the FMO fragment size and the CIM subsystem parameter ζ, calculations were performed using two and four alanine residues per FMO fragment (five-and ten-fragment schemes) while also varying the subsystem size parameter ζ from 0.003 to 0.001 hartree.…”
Section: Preliminary Calculations and Discussionmentioning
confidence: 99%
“…The MP2 subsystem calculations were performed in parallel using one core for each subsystem. The FMO2-CIM/MP2 and CIM/MP2 methods both generated 256 or fewer total subsystems for Ala 20 , except in the case of the ten-fragment, ζ = 0.001 FMO2-CIM/MP2 calculation. (See Table 1.).…”
Section: Preliminary Calculations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is also closely related to PNO methods, except here our special virtual orbitals are labelled by a single occupied index, rather than by a pair of occupied orbitals. This can be expected to confer improved efficiency in integral transformation, even when density fitting is used, 5,6 and also makes extension to odd-order excitations more obvious.…”
Section: Orbital-specific Virtual Mp2mentioning
confidence: 99%
“…This can be achieved, however, through the use of pair natural orbitals (PNOs), introduced by Edmiston and Krauss 3 and pioneered as a general method for molecular correlation theories in Meyer's development of the coupled-electronpair approximation. 4 The approach has recently returned to prominence through the work of Neese and co-workers 5,6 and Tew et al have recently demonstrated how the PNO concept can be extended to increase the efficiency of resolution of identity approximations in explicitly correlated F12 theories. 7 An alternative proposed by Pulay and Saebø is the use of fixed domains of projected atomic orbitals (PAOs) for a) Electronic mail: kura@ims.ac.jp.…”
Section: Introductionmentioning
confidence: 99%